2018
DOI: 10.3892/ol.2018.9062
|View full text |Cite
|
Sign up to set email alerts
|

A study on the biological function of heat shock factor 1 proteins in breast cancer

Abstract: The present study aimed to investigate the effect of HSF1 proteins on cell proliferation, apoptosis and invasion of breast cancer. The Michigan Cancer Foundation-7 (MCF-7) HSF1-knocked down stable cell line (experimental group) and control cell line (control group) were obtained using a lentivirus assay, and the effects of HSF1 knockdown on the proliferation, tumor formation, apoptosis and invasion ability were analyzed, respectively. The effects of HSF1 on downstream signals were analyzed using western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In fact, the increased expression and activity of HSF1 are observed in a variety of cancers, such as prostate and breast cancers, in advanced stages, suggesting HSF1 as an important regulator of tumor progression and metastasis [79][80][81][82][83]. As the upstream modulator of various pathophysiological proteins such as HSP70, HSP90, MIF, Bcl2, and Bax, HSF1 assists in multiple parts of malignancy, including proliferation, migration, invasion, and inhibition of apoptosis [84,85]. Furthermore, HSF1 functions to allow cancer cell formation and progression by inducing genomic instability and stabilizing mitotic spindle organization through regulation of Cyclin D, p21, and p27 during mitosis [86][87][88].…”
Section: Role Of Hsf1 In Cancer Developmentmentioning
confidence: 99%
“…In fact, the increased expression and activity of HSF1 are observed in a variety of cancers, such as prostate and breast cancers, in advanced stages, suggesting HSF1 as an important regulator of tumor progression and metastasis [79][80][81][82][83]. As the upstream modulator of various pathophysiological proteins such as HSP70, HSP90, MIF, Bcl2, and Bax, HSF1 assists in multiple parts of malignancy, including proliferation, migration, invasion, and inhibition of apoptosis [84,85]. Furthermore, HSF1 functions to allow cancer cell formation and progression by inducing genomic instability and stabilizing mitotic spindle organization through regulation of Cyclin D, p21, and p27 during mitosis [86][87][88].…”
Section: Role Of Hsf1 In Cancer Developmentmentioning
confidence: 99%
“…The mRNA levels of hsf1 and sp1 showed identical in runx1 GFP + cells and in runx1 GFP − cells, and maintained stable in runx1 GFP + cells after Cu stresses ( Figure S10 E). However, SP1, MYC-SP1, or MYC-HSF1 ChIP-qPCR analyses showed that SP1 or HSF1 signals were less enriched at the promoter of FOXM1 in Cu-stressed group compared with the control ( Figures 8 C2-8C4), and Cu overload significantly up-regulated expression of HSF1 negative target BAX 44 , 45 while significantly down-regulated expressions of HSF1 positive target CDC6 and CKS1B 46 and SP1 positive targets CDC25A 47 and MYCA 48 ( Figure 8 D).…”
Section: Resultsmentioning
confidence: 98%